Itinerários da vida de solteira: razões e sentidos em projetos de vida de mulheres solteiras à luz do sintagma identidade-metamorfose-emancipação - Antunes, Mariana Serafim Xavier (2010)
This dissertation addresses the disclosure of a supposed itinerary of female single life conjectured by the production of a discourse, broadcast in mass communication media on a new social character: the new single female . Apparently, the notions about this new single female can build a political identity seeking recognition of new meanings to the character, who is then promoted as the protagonist of contemporary social changes. In a context of pluralism, it also seems to substantiate a process of social individualization. Interests linked to this proposed cultural enhancement, when based on instrumental purposes, may trigger greater disparities to access and participate in social, economic and cultural benefits, and highlight unequal relationships already established among social actors. In these cases, the restoration of the single female character seems to distance itself from the notion of an identity proposal of autonomous character. Contrarily, it is designed as an option among excluding and discriminatory choice possibilities. Thus, this research seeks to understand the reasons and directions laid out by these women regarding their life projects. This study is proposed within the field of Critical Social Psychology, in which we aim at covering, in the light of the sintagm Identity-Metamorphosis-Emancipation, potential pitfalls that such itinerary may give an emancipatory utopia. Moreover, we seek to recognize in lifestories the movements to overcome the restrictive conditions identified through a historical context that, in turn, provided us with information to discuss the possibility to strengthen the autonomy of women nowadays